2019
DOI: 10.5194/nhess-19-1129-2019
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of an extreme weather event in a hyper-arid region using WRF-Hydro coupling, station, and satellite data

Abstract: Abstract. This study investigates an extreme weather event that impacted the United Arab Emirates (UAE) in March 2016, using the Weather Research and Forecasting (WRF) model version 3.7.1 coupled with its hydrological modeling extension package (WRF-Hydro). Six-hourly forecasted forcing records at 0.5∘ spatial resolution, obtained from the National Center for Environmental Prediction (NCEP) Global Forecast System (GFS), are used to drive the three nested downscaling domains of both standalone WRF and coupled W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 61 publications
5
45
0
Order By: Relevance
“…As was the case for the winter period, and in line with other studies such as Gunwani and Mohan (2017), both WRF and NICAM generally underestimate the observed cloud cover, as concluded by visually comparing the two (not shown) and in line with other studies such as Schwitalla et al (2019) and Wehbe et al (2019), leading to enhanced downward shortwave radiation fluxes at the surface and warmer daytime air temperatures. The exception is when heavier than observed precipitation amounts are predicted, as seen by comparing Figs.…”
Section: June 2020supporting
confidence: 88%
See 4 more Smart Citations
“…As was the case for the winter period, and in line with other studies such as Gunwani and Mohan (2017), both WRF and NICAM generally underestimate the observed cloud cover, as concluded by visually comparing the two (not shown) and in line with other studies such as Schwitalla et al (2019) and Wehbe et al (2019), leading to enhanced downward shortwave radiation fluxes at the surface and warmer daytime air temperatures. The exception is when heavier than observed precipitation amounts are predicted, as seen by comparing Figs.…”
Section: June 2020supporting
confidence: 88%
“…This is confirmed when the predicted cloud amounts are visually compared with those given by the Spinning Enhanced Visible and Infrared Imager (SEVIRI; Schmetz et al 2002) instrument (not shown). A similar result was obtained by Gunwani and Mohan (2017) (2019) noted a tendency of WRF to generate less clouds than those observed over the UAE for a summertime convective event, and Wehbe et al (2019) for an extreme event in the cold season. NICAM has also been found to underpredict the observed cloud amounts, in particular, midtropospheric clouds (e.g., Kodama et al 2012).…”
Section: B Cold Season Event (16-18 December 2017)supporting
confidence: 81%
See 3 more Smart Citations